Dietary diversity and mental health in preschoolers in rural China - Li, Shaoping; Chen, Kevin Z.; Liu, Chengfang; Bi, Jieying; He, Zhenya; Luo, Renfu; Yu, Yanying; Wang, Zimeiyi (Cambridge University Press, 2021)
To investigate the prevalence of mental health problems among preschoolers in rural China and examine the relationship between dietary diversity and mental health.A cross-sectional survey analysis was performed. Child mental health was assessed with the Strengths and Difficulties Questionnaire (SDQ). Child dietary diversity was assessed with the dietary diversity score (DDS), which was calculated based on nine food groups using a 24-h recall method. Data were analysed using unadjusted and adjusted logistic regression models.Two nationally designated poverty counties in Hunan Province of China.Preschoolers (n1334) aged 3–5 years, preschools (n26).Of 950 preschoolers with data on both dietary diversity and mental health, 663 (70 %) were classified as having at least one kind of mental health problem. The prevalences of emotional symptoms, conduct problems, symptoms of hyperactive/inattention, peer relationship problems and poor prosocial behaviour were 39, 27, 23, 12 and 26 %, respectively. Male preschoolers showed higher risks of having mental health problems than their female counterparts on each SDQ subscale except for conduct problems. Moreover, a higher DDS was significantly associated with a lower likelihood of having symptoms of hyperactivity/inattention, peer relationship problems and prosocial behaviour problems after adjustment for confounders (preschoolers’ age, gender, cognitive ability, parental migration status, primary caregiver’s education and household socio-economic status).The prevalence of mental health problems was high among preschoolers in rural China. Improving child dietary diversity might be an important strategy to consider in the design of interventions to improve child mental health.